Monitoring of wind effects on 600 m high Ping-An Finance Center during Typhoon Haima. (15th July 2018) - He, Yinghou; Han, Xuliang; Li, Qiusheng; Zhu, Hongping; He, Yuncheng
Highlights: Monitor wind effects on a 600 m high skyscraper during Typhoon Haima. Investigate typhoon generated cladding pressures on the skyscraper. Investigate structural acceleration responses and modal parameters during the typhoon. Comparing the measured mode shapes and natural frequencies with predictions by FEM. Evaluate serviceability of the skyscraper under typhoon condition. Abstract: This paper presents analyzed results of field measurements of wind-induced pressures on building claddings and structural responses of 600 m high Ping-An Finance Center (PAFC) in Shenzhen, China during the passage of Typhoon Haima. The characteristics of cladding pressures during the typhoon were investigated with highlights on energy distribution, non-Gaussian probability and coherence features. Then, the natural frequencies, damping ratios and mode shapes of the skyscraper were presented. Based on the field measurements, the amplitude-dependent characteristics of the modal parameters were discussed and the range of selection of damping ratio for the wind-resistant design of super-tall buildings was recommended. Finally, the serviceability of the skyscraper under typhoon condition was assessed. This paper aims to further understand the wind effects on super-tall buildings and provide useful information for the design of skyscrapers in tropic cyclone prone regions.